Carving and Ornamentation of the Pilaster Base - Temples of India Project Team (Jio Institute, 2024)
Details of the carving and ornamentation of the pilaster base, which is in the west, south and north-facing elevations of the temple. The pilasters are identical in design. They have a wider base, slender and are relatively plain. The pilaster base has an elongated vertical floral motif with a horizontal band of diamond-like motifs.